2022
DOI: 10.1002/hsr2.581
|View full text |Cite
|
Sign up to set email alerts
|

Sputum neutrophil elastase and its relation to pediatric bronchiectasis severity: A cross‐sectional study

Abstract: Background and Aims: Sputum neutrophil elastase (NE) is a marker of neutrophilic airway inflammation in bronchiectasis. Yet, not much is known about its role in pediatric bronchiectasis severity. This study aimed to assess the sputum NE value as a biomarker of clinical and radiological severity in pediatric bronchiectasis.Methods: This was a cross-sectional study assessing sputum NE in a total of 50 bronchiectasis patients under the age of 18 years-30 patients with cystic fibrosis (CF) and 20 patients with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Another recent pediatric cross-sectional study of both CF and non-CF related bronchiectasis also found that sputum NE significantly correlated with exacerbation severity and frequency, as well as number of hospitalizations ( 77 ). For CF bronchiectasis it was specifically observed that NE correlated with risk of disease progression and increased lung function decline, while for non-CF bronchiectasis, sputum NE positively correlated with airway neutrophil counts and severity of lung disease ( 77 ). Asthma is a chronic lung disease with a much broader range of inflammatory phenotypes, and while eosinophil activity is critical to some cohorts, some of the more severe forms of asthma are primarily a result of airway neutrophilic inflammation ( 78 ).…”
Section: Neutrophils Drivers Of Lung Damagementioning
confidence: 98%
See 1 more Smart Citation
“…Another recent pediatric cross-sectional study of both CF and non-CF related bronchiectasis also found that sputum NE significantly correlated with exacerbation severity and frequency, as well as number of hospitalizations ( 77 ). For CF bronchiectasis it was specifically observed that NE correlated with risk of disease progression and increased lung function decline, while for non-CF bronchiectasis, sputum NE positively correlated with airway neutrophil counts and severity of lung disease ( 77 ). Asthma is a chronic lung disease with a much broader range of inflammatory phenotypes, and while eosinophil activity is critical to some cohorts, some of the more severe forms of asthma are primarily a result of airway neutrophilic inflammation ( 78 ).…”
Section: Neutrophils Drivers Of Lung Damagementioning
confidence: 98%
“…Sputum NE was elevated during exacerbations and reduced in response to antibiotic therapy targeting organisms such as P. aeruginosa and H. influenzae, highlighting a relationship between release of NE and bacterial respiratory infection (76). Another recent pediatric cross-sectional study of both CF and non-CF related bronchiectasis also found that sputum NE significantly correlated with exacerbation severity and frequency, as well as number of hospitalizations (77). For CF bronchiectasis it was specifically observed that NE correlated with risk of disease progression and increased lung function decline, while for non-CF bronchiectasis, sputum NE positively correlated with airway neutrophil counts and severity of lung disease (77).…”
Section: Neutrophils Drivers Of Lung Damagementioning
confidence: 98%
“…BAL fluid has been considered the gold standard for clinicians to assess infection and inflammation in the lungs, with secretions providing an optimal source of inflammatory cells directly from the lower airway [104]. Research has shown that neutrophil elastase from BAL predicted pulmonary exacerbations in young children with cystic fibrosis [105].…”
Section: Bal Fluidmentioning
confidence: 99%
“…Unlike BAL fluid, expectorated sputum has been used as a less invasive alternative to measure airway inflammation [110]. The measurement of sputum neutrophil elastase has been suggested as a promising biomarker for bronchiectasis severity, with increased levels indicating the need for aggressive management [104]. However, most children have difficulties in expectorating, and most downstream assessments of sputum require a large yield.…”
Section: Sputummentioning
confidence: 99%
See 1 more Smart Citation